Thoughts for the times. On war and death” of Sigmund Freud: a century later. - Fuks, Betty Bernardo (2017)
This article proposes to reflect on the relevance of the Freudian text 1915 - “Thoughts for the times on war and Death” from some metapsychological concepts that gave substance to the criticism of the author analysis the civilization that produced the First World War. Assuming the hypothesis that text is a leit motiv to the construction of the concept of death drive, we hold that psychoanalytic theory, be subject to constant and plural reworking, does not stop to call the analyst to reflect on the social and politic configuration that lives.